Bi-Ag-Sulfosalts and Sulfoarsenides in the Ruwai Zn-Pb-Ag Skarn Deposit, Central Borneo, Indonesia - Dana, Cendi D. P.; Agangi, Andrea; Idrus, Arifudin; Lai, Chun-Kit; Simbolon, Doly R. (MDPI, 2022)
The Ruwai skarn deposit is located in the Schwaner Mountain complex within the central Borneo gold belt and is currently considered the largest Zn skarn deposit in Indonesia. The deposit has been known to host Zn-Pb-Ag mineralization in the form of massive sulfide ore bodies; however, the occurrence of Ag-bearing minerals has not been identified yet. This study documents the mineralogical characteristics of several Bi-Ag sulfosalts and sulfoarsenides, as well as their chemical compositions. Ten Bi-Ag sulfosalts were identified, including native bismuth, tetrahedrite, cossalite, tsumoite, bismuthinite, joseite-B, Bi6Te2S, Bi-Pb-Te-S, Bi-Ag-S, and Bi-Te-Ag. Three sulfoarsenides were identified, including arsenopyrite, glaucodot, and alloclasite. The occurrence of Bi-Ag sulfosalts is typically associated with massive sulfide mineralization, although tsumoite can also be found associated with massive magnetite. In terms of sulfoarsenides, both arsenopyrite and glaucodot are associated with massive sulfide mineralization, whereas alloclasite is associated with massive magnetite mineralization. The Bi-bearing minerals are characterized by irregular, bleb-like texture or patch morphology, and occur either as free grains or inclusions within sulfides, such as galena or pyrite. Tetrahedrite typically has an anhedral shape with a rim or atoll texture surrounding sphalerite or galena. In contrast, sulfoarseni-des are typically found as euhedral–subhedral grains where glaucodot typically is rimmed by arsenopyrite. Both Bi-Ag sulfosalt and sulfoarsenides were formed during the retrograde stage under high oxidation and a low sulfidation state condition. The ore-forming temperature based on arsenopyrite geothermometry ranges from 428◦C to 493◦C.